The Low Prevalence of Y Chromosomal Microdeletions is Observed in the Oligozoospermic Men in the Area of Mato Grosso State and Amazonian Region of Brazilian Patients - Gleice Cristina dos Santos Godoy; Bianca Borsatto Galera; Claudinéia Araujo; Jacklyne Silva Barbosa; Max Fernando De Pinho; Marcial Francis Galera; Sebastião Freitas de Medeiros (SAGE Publishing, 2014)
Objective To determine the prevalence of chromosomal abnormalities and microdeletions on Y chromosome in infertile patients with oligozoospermia or azoospermia in Mato Grosso state, Brazil. Methods This cross-sectional study enrolled 94 men from infertile couples. Karyotype analysis was performed by lymphocyte culture technique. DNA from each sample was extracted using non-enzymatic method. Microdeletions were investigated by polymerase chain reaction (PCR). Results With the use of cytogenetic analysis, five patients (5.3%) had abnormal karyotype, one azoospermic patient (1.1%) had karyotype 46,XY,t(7;1) (qter-p35), one (1.1%) with mild oligozoospermia had karyotype 46, XY, delY(q), and two other azoospermic patients had karyotype 47,XXY, consistent with Klinefelter syndrome (KS). One of them (1.1%) with severe oligozoospermia had karyotype 46,XY,8p+. Microdeletion on Y chromosome was found in the azoospermia factor c (AZFc) region in only one azoospermic patient (1.1%). Conclusions The prevalence of genetic abnormalities in oligo/azoospermic Brazilian men from infertile couple was 5.3%, and microdeletion on Y chromosome was not a common finding in this population (1.1%).